Photooxidising activity of titanium dioxide – nickel heteropolymolybdate and titanium dioxide – molybdenum trioxide coatings under natural lighting conditions - Sviridova, Tatsiana V.; Agabekov, Vladimir E.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2024)
It has been shown that in passing from bare titania-based thin-film photocatalysts to photacatalytic coatings based on TiO2:NiMo6O24H64– and TiO2/MoO3 composites the oxidation activity exhibits 9-fold increase under conditions of the long-term (10 days) illumination with solar light in the day-to-night cycle. The observed effect results from the increased photocharge separation efficiency at the heterojunctions, as well as from the generation of peroxo species as the oxidation agent capable to ensure the post-exposure oxidation at the photocatalyst surface.
Keywords: photocatalysts; titanium dioxide; molybdenum trioxide; heteropolymolybdate; solar illumination